Suitability water quality parameters for Eucheuma cottonii culture at Majene Waters - Arbit, Nur Indah Sari; Lestari, Dian; Erwin, Erwin; Carong, Supajo Razasli; Syamsudin, Fadli; Mannan, Abdul; Thabrani, Mulihartati (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Seaweed cultivation in Majene Regency, West Sulawesi, has not experienced significant development as in neighboring Polewali Mandar and Mamuju Regency. This can be seen from the absence of active seaweed cultivation activities in Majene Regency. The aim of this research is to assess the physical and chemical aspects of water to determine the suitability of locations for cultivating Eucheuma cottonii seaweed in Majene waters. The method used to measure ecological suitability included parameters such as temperature, salinity, dissolved oxygen (DO), pH, phosphate, nitrate and salinity. Subsequently, the data is scored to determine suitability classes: suitable (S1) with values ranging from 37 to 48, moderately suitable (S2) with values between 36 and 25 and non sultable (S3)/N) with value 25. The results showed that after applying weighting and scoring, locations such as East Banggae, Pamboang 1, Tubo Sendana, and Sendana 2 showed suitable scoring result with scores of 39, 39, 40, and 40. While locations such as Pamboang 2, Pamboang 3, Malunda, and Sendana 1 showed moderately suitable scoring results with scores of 33, 33, 34 and 36. Majene waters have potential areas for seaweed cultivation based on classes S1 (suitable) and S2 (moderately suitable).Keywords:SeaweedMajene WatersLocation SuitabilityWater QualityAquaculture